P66 Standardising strengths of unlicensed medicines in a large London hospital trust. Issue 9 (19th August 2020) - Lo, Alice; Benn, Chloe
Abstract : Background: A UK national position statement on standardised strengths of unlicensed liquid medicines recommend that when children require unlicensed liquid medications, they should receive the recommended strength. By standardising strengths of these medicines, the risk of errors being made in the doses given to children will be reduced and prevent accidental under and overdoses. 1 Our Trust has 4 hospital sites since merging in 2012, we found the process of switching to a standard strength far from simple. Methods: The strengths of unlicensed liquid medicines listed in the position statement available on the pharmacy dispensing system (JAC) were identified, along with the speciality users. Pharmacy and clinical leads were consulted for agreement to switching to the standardised strengths. Pharmacy procurement identified new products in standardised strengths and products were reviewed for suitability by paediatric pharmacist. A cost impact analysis was carried out. Communication was sent to stakeholders including, doctors, nurses, pharmacy and primary care. Results and Discussion: We found the standardised strengths of azathioprine, clonazepam, ethambutol, isoniazid, melatonin, omeprazole, phenobarbitone and pyrazinamide strengths were on formulary. Clopidogrel, hydrocortisone, sertraline and tacrolimus liquids are not used. Different strengths of the listed unlicensed liquid medicines were used by different sites and specialties. Lead speciality pharmacists agreed with the standardisation. We identified use of unlicensed products where licensed products are available (sildenafil 20 mg/5 mL and furosemide 5 mg/5 mL). We added the use of these items to our review. We were not able to agree on a single standard strength for some items; the neonatal intensive care unit (NICU) have babies under 500 g who may require furosemide, spironolactone and sildenafil in doses that measure less than 0.1 mL using the recommended strengths. This volume is deemed less than satisfactory to be measured safely 1 . It has been agreed with the neonatal lead pharmacist that additional strengths of the sildenafil (unlicensed 20 mg/5 mL), spironolactone (unlicensed 10 mg/5 mL) and furosemide (20 mg/5 mL) be available for inpatient NICU use only. The potential for patients to be discharged on the non-standard strength is reduced by specifying 'Not for discharge - inpatient use only' on the pharmacy system as well as having them only as NICU stock from medicines distribution. Patients admitted on other strengths will be switched (with consent); to minimise risk pharmacists will ensure carers are aware of the change & correct dose volume to administer and endorse TTAs noting the change in concentration for the GP. Primary care have been engaged with the switch and invited the consultant pharmacist to discuss this at the interface meeting. We were not able to source the recommended midazolam 10 mg/5 mL. The switch to chloral hydrate to 1 g/5 mL was calculated to have a significant cost pressure therefore it was agreed that that we would not change from chloral hydrate 500 mg/5 mL at this time as it is mainly used in the in-patient setting within our Trust. Based on current usage there is an estimated cost saving of over £5 k based on the switch of sodium chloride, sildenafil, furosemide and spironolactone. The impact will be reviewed in 6 months. Conclusion: A successful switch requires a team approach but will benefit patient safety and save money. Reference: The Neonatal and Paediatric Pharmacists Group (NPPG) and Royal College of Paediatric and Child Health (RCPCH). Position statement 18–01 Using Standardised Strengths of Unlicensed Liquid Medicines in Children. Version 2. May 2019.